2021
DOI: 10.3390/chemengineering5040069
|View full text |Cite
|
Sign up to set email alerts
|

Application of Gold Nanoparticle-Based Materials in Cancer Therapy and Diagnostics

Abstract: Several metal nanoparticles have been developed for medical application. While all have their benefits, gold nanoparticles (AuNPs) are ideal in cancer therapy and diagnosis as they are chemically inert and minimally toxic. Several studies have shown the potential of AuNPs in the therapeutic field, as photosensitizing agents in sonochemical and photothermal therapy and as drug delivery, as well as in diagnostics and theranostics. Although there is a significant number of reviews on the application of AuNPs in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 194 publications
(212 reference statements)
0
7
0
Order By: Relevance
“…Various authors have also created systems in which nano MOFs (NMOFs) can be successfully used as antibacterial agents, both as prophylactic or therapeutic agents, thus offering significant advantages in diagnosis, monitoring, and therapy. Therefore, in the following sections, given the highly cited potential biomedical applications of nanomaterials [7,8,43,114], we review the potential applications of MOFs.…”
Section: Biomedical Applications Of Mofsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various authors have also created systems in which nano MOFs (NMOFs) can be successfully used as antibacterial agents, both as prophylactic or therapeutic agents, thus offering significant advantages in diagnosis, monitoring, and therapy. Therefore, in the following sections, given the highly cited potential biomedical applications of nanomaterials [7,8,43,114], we review the potential applications of MOFs.…”
Section: Biomedical Applications Of Mofsmentioning
confidence: 99%
“…Nanoparticles are a relatively new material in the medical field, but over the years they have become more and more relevant, since they have a very wide range of applications due to their different nature. Metal nanoparticles can be actively used as antibacterial, cytotoxic, and diagnostic materials [7][8][9][10]. Polymer nanoparticles can also be used as drug delivery systems to diagnose and treat various diseases [4,11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggested that AuNPs less than 20 nm exhibited surface plasmon resonance (SPR) with negligible scattering characteristics [3,4]. In contrast, large AuNPs between 20 and 80 nm display increased scattering characteristics of these materials [5][6][7]. Many studies demonstrated the colloidal nature of spherical AuNPs, which appeared red with surface plasmon resonance (SPR) band observed at 520 nm, which depends on AuNP interparticle distance, surrounding media refractive index, shape, and size [8][9][10].…”
Section: Tunable Optical Propertiesmentioning
confidence: 99%
“…Photoacoustic imaging (PAI)—a biomedical analysis technique that provides actionable information about the molecular characteristics of tissue—is a recently developed hybrid biomedical imaging technique for monitoring tumor angiogenesis and detecting skin melanoma, as well as for monitoring and diagnosing various other neoplasms [ 111 ].…”
Section: Main Applications Of Biodegradable Polymeric Nanoparticlesmentioning
confidence: 99%